2013
DOI: 10.1371/journal.pone.0080549
|View full text |Cite|
|
Sign up to set email alerts
|

Impacts of Agricultural Practices on Insecticide Resistance in the Malaria Vector Anopheles arabiensis in Khartoum State, Sudan

Abstract: BackgroundAgricultural pesticides may play a profound role in selection of resistance in field populations of mosquito vectors. The objective of this study is to investigate possible links between agricultural pesticide use and development of resistance to insecticides by the major malaria vector Anopheles arabiensis in northern Sudan. Methodology/Principal FindingsEntomological surveys were conducted during two agricultural seasons in six urban and peri-urban sites in Khartoum state. Agro-sociological data we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
34
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 33 publications
1
34
0
Order By: Relevance
“…DDT is still approved for IRS use by WHO and remains in use in some locations, however within the last two decades pyrethroid use has been far more common and widespread. DDT was also used in agriculture from the 1940s, and although agricultural usage has greatly diminished since the 1970s, some usage remains [27]. In this study we reported evidence of positive selection on the and alleles, as well as the combination and possibly .…”
Section: Discussionmentioning
confidence: 52%
“…DDT is still approved for IRS use by WHO and remains in use in some locations, however within the last two decades pyrethroid use has been far more common and widespread. DDT was also used in agriculture from the 1940s, and although agricultural usage has greatly diminished since the 1970s, some usage remains [27]. In this study we reported evidence of positive selection on the and alleles, as well as the combination and possibly .…”
Section: Discussionmentioning
confidence: 52%
“…Agricultural pesticides often belong to the same classes as those used for vector control [7,11]. Thus, they can affect the susceptibility of vector populations by increasing the frequencies of existing resistance mechanisms, or by selecting new mechanisms [11][12][13][14]. Because these selective pressures are heterogeneous, resistance frequency and its effect on vector control could vary from one population to another and over time [12].…”
Section: Introductionmentioning
confidence: 99%
“…gambiae s.s.) [85] at frequencies approaching those in An. arabiensis from Ethiopia and Sudan [86] , [87] . An.…”
Section: Discussionmentioning
confidence: 99%